The Form of the Unfinished : English Poetics from Spenser to Pound - Rajan, Ballachandra (Book collections on Project MUSE., 2014)
Distinguishing between the incomplete poem and the unfinished poem, Professor Rajan sees the unfinished poem as remaining in dialogue with its own dissensions. He contributes to current critical debates by showing how the long poem resists assimilation to the forces of both unification and undecidability, finding its significance on the line of engagement between them. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton Unive.